The development of knowledge sharing culture in the construction industry - Low, Lisa Seow Wei (2007)
This research aims to identify the determinants that promote the development of knowledge sharing culture in the construction industry. The construction industry is, unlike any other industries, which have hidden reservoirs of intelligence that remain largely untapped and unionized. Construction sector is fragmented and characterized by small and medium size organizations shall accommodate an interesting avenue for tapping into this hidden asset to capitalize on what collective organizations concern. Right organization characteristics along with right work practices are conducive to knowledge sharing which in turn influence the employees’ behaviour. Consequently, there are four objectives of this study. First objective is to identify the practices for factors that promote the development of knowledge sharing culture. Second objective is to identify the preferred practices for each factor that promotes the development of knowledge sharing culture. Third objective is to investigate the relationship between the factors and the development of knowledge sharing culture. And finally, to investigate the relationship between the practices and the development of knowledge sharing culture. For the purpose of this study, six units of construction organizations in Sarawak are investigated through two major approaches which comprised of case study and questionnaire survey. Descriptive analysis, frequency analysis and one-sample t test analysis are applied to analyze the factors, practices and their significant relationship in promoting knowledge sharing culture. From the literature review, eight factors and 51 practices are identified as the determinants that promote the development of knowledge sharing culture. These factors and practices are verified through the case study interviews. Some 34 practices out of 51 practices being surveyed are identified as the preferred practices which act as promoters of knowledge sharing culture. The result of one-sample t test shows that the factor of strategy, structure, support mechanism, management development, communication, trust, motivation, learning and all the 51 identified practices are the contributing determinants that promote the development of knowledge sharing culture